Belarusian problems in Polish literature of 1918‒1939: embodiment strategies - Khmialnitski, Mikalai M. (Journal of the Belarusian State University. Philology, 2021)
The article attempts to reveal the major ideological and artistic strategies for the embodiment of Belarus’ problems in Polish literature of 1918–1939, and is based on the works of the writers of the period associated with Belarus (M. Rodziewiczówna, M. Wańkowicz, J. Bułhak, K. Zdziechowski, J. Czechowicz, etc.). The paradigm components and levels of creative picturing of Belarusian motives, images and realities are identified and characterised, namely: the historical homeland; birthplace; borderland space; cultural landscape, Belarusian heroes; autochthonous population’s traditions and customs; nature; and the presence and role of Belarusian words in the works of the above writers. Three forms of Polish writers’ manner of addressing Belarusian topics have been identified and justified, namely: Belarus as a birthplace; a biography fact of a native Pole; and a historical and cultural (literary) allusion. The article focuses on the fact that the artistic literary world of many Polish writers of the interwar period (1918–1939) was formed basically by Belarusian factors in the process of literary interaction and intercultural dialogue.